Comparative safety and effectiveness of ticagrelor versus clopidogrel in patients with acute coronary syndrome. An on treatment analysis from the multicenter CREA ARIAM Andalucia registry. (2nd May 2022) - Hernandez-Meneses, B; Padilla-Rodriguez, G; Carmona-Carmona, J; Hidalgo-Urbano, R; Almendro-Delia, M; Garcia-Rubira, JC
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): This study was financially by a non conditional grant by Astrazeneca. Background/Introduction: The favorable net clinical benefit of ticagrelor over clopidogrel in the PLATO trial has been recently questioned in observational studies. However, these mostly retrospective analyses based on the intention-to-treat (ITT) principle, systematically failed to account for switching between P2Y12 inhibitors, which may indeed have led to biased estimates due to exposure misclassification (incorrect classification of subjects with respect to exposure) Purpose: To assess the on-treatment safety and effectiveness of ticagrelor vs clopidogrel among patients with acute coronary syndrome (ACS) in a non-trial scenario. Methods: Prospective multicentre cohort study of 2070 ACS patients discharged on ticagrelor or clopidogrel between 2015 and 2019. Major exclusions were previous intracranial bleeding, use of prasugrel or oral anticoagulation. Primary study hypothesis stated safety profile of ticagrelor is not unacceptably worse (not inferior) than that of clopidogrel. Primary outcome was risk of major bleeding (BARC types 3, 5) at 1 year. Secondary outcomes were major adverse cardiac and cerebrovascular events (MACCE), and net adverse clinical event (NACE) at 1-yer. Association of ticagrelor vs clopidogrel with outcomes was evaluated based on the on-treatment principle using fully-adjusted Cox regression models with double robust inverse probability of censoring weighted (IPCW) estimators. Sensitivity analyses included propensity score matching analysis and ITT simulation analysis. Results: Among 2070 patients included (mean age 63 years, 73% men), 1035 were discharged on ticagrelor and clopidogrel in each treatment group, respectively. Ticagrelor-treated patients were younger, had less comorbidities and more often underwent percutaneous coronary intervention over coronary artery bypass grafting surgery, as the preferred revascularization choice. After adjust for medication adherence and switching, ticagrelor did not increase the risk for major bleeding compared with clopidogrel (adjusted hazard ratio 1.40, 95% CI 0.96 – 2.05; P = .075). Although there was signal for potential harm with ticagrelor among elderly people and patients with previous bleeding, exploratory analysis suggested consistent reductions in MACCE and NACE risks compared with clopidogrel. PSM analysis was congruent with primary analysis, whereas ITT analysis yielded results in the opposite direction. Conclusion(s): In this on-treatment analysis of an all-comers ACS population, ticagrelor did not pose an increased risk for major bleeding, while resulted in a net clinical benefit compared with clopidogrel. Further studies accounting for drug switching are warranted to confirm these findings in high-bleeding risk populations.